Cervical insufficiency with bacterial vaginosis and vulvovaginitis in pregnancy: Prevention - Gavxaroy Baxtiyorjon kizi Yusupova (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2025)
Bacterial vaginosis (BV) and vulvovaginitis are common vaginal infections that can significantly affect pregnant women, particularly those with cervical insufficiency (CI). Cervical insufficiency is a condition where the cervix weakens and opens prematurely, often resulting in preterm birth or pregnancy loss. This article explores the relationship between BV, vulvovaginitis, and CI, focusing on their shared pathophysiological mechanisms and their combined impact on pregnancy outcomes. BV, characterized by an imbalance in vaginal microbiota, and vulvovaginitis, which involves inflammation of the vulva and vagina, can increase the risk of infection ascending to the upper reproductive tract, potentially exacerbating cervical insufficiency and increasing the risk of preterm birth. The review emphasizes the importance of early detection, timely treatment, and preventive measures such as antibiotic prophylaxis, good hygiene practices, and regular prenatal monitoring to manage these infections in pregnant women with cervical insufficiency. By addressing these infections, healthcare providers can improve maternal and fetal health outcomes, reducing the risks associated with preterm labor and other pregnancy complications.